AJARAN â€œILMU KANTONG BOLONGâ€ DAN PANDANGAN HIDUP PANCASILA DALAM PERSPEKTIF ETIKA SOSIAL - Mulyono, Mulyono (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper is study in Ethics. This study compared two moral teaching in Sosokartonoâ€™s â€œIlmu Kantong Bolongâ€ and way of life â€œPancasilaâ€. From the comparation it was found that both the moral teachings of basing itself on human nature, so that both the moral teachings are humanist and paractical. If both are capable of moral teachings internalized and actualized into the behavior of Indonesian peoples, then the problem of demoralization and a crisis of identity faced by Indonesia to day can be overcome. Although the struggle for overcome the problem is extraordinary seriousness struggle becaused swift currents of globalization engulfing all nations. Keywords: Ethics, comparation, moral teaching, actualization, demoralization, be overcome.